The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jaal.1017
|View full text |Cite
|
Sign up to set email alerts
|

Seal of Biliteracy Graduates Get Critical: Incorporating Critical Biliteracies in Dual‐Language Programs and Beyond

Abstract: Research has suggested that U.S. K–12 dual‐language and Seal of Biliteracy programs do not benefit all students equally in their recognition of students’ multilingual competencies. The authors explored the perspectives of high school Seal of Biliteracy graduates: how they conceptualized the seal and the benefits that they had or had not derived from attaining it. Through a framework of critical biliteracies, the authors drew on interview data with Seal of Biliteracy graduates to highlight the dynamics of cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…These synergies extend to language education, where a poststructural perspective can be used to interrogate subject positions such as "English learner," not as neutral descriptive labels, but as power hierarchies that produce Englishdominance as an unquestioned norm (Koslowski, 2018). These hierarchies are often racialized in regard to which students receive remedial labels as a result of their bilingualism (almost exclusively students of color), as opposed to students whose multilingual repertoires are framed as cosmopolitan or as giftedness (often white students; see Colomer & Chang-Bacon, 2020). The English learner label also produces racialized assumptions of "foreignness" or immigration status in U.S. contexts, despite the majority of emergent bilinguals having been born in the U.S. (García & Kleifgen, 2018).…”
Section: Poststructural Theories Of Race and Languagementioning
confidence: 99%
“…These synergies extend to language education, where a poststructural perspective can be used to interrogate subject positions such as "English learner," not as neutral descriptive labels, but as power hierarchies that produce Englishdominance as an unquestioned norm (Koslowski, 2018). These hierarchies are often racialized in regard to which students receive remedial labels as a result of their bilingualism (almost exclusively students of color), as opposed to students whose multilingual repertoires are framed as cosmopolitan or as giftedness (often white students; see Colomer & Chang-Bacon, 2020). The English learner label also produces racialized assumptions of "foreignness" or immigration status in U.S. contexts, despite the majority of emergent bilinguals having been born in the U.S. (García & Kleifgen, 2018).…”
Section: Poststructural Theories Of Race and Languagementioning
confidence: 99%
“…We have known that nuances of SoBL policies vary by state with implications for students’ access to the award and equity in demonstrating language competencies (Davin & Heineke, 2017; Subtirelu et al., 2019; Valdés, 2020). But our findings suggested that amid formal legislation that may support or deter efforts to recognize students’ biliteracy, district leaders appropriated policies in creative ways, such as situating the SoBL within dual‐ and heritage‐language programs, attaching to credit‐by‐exam initiatives, or maximizing assessment options (Borowczyk, 2019; Colomer & Chang–Bacon, 2019; Fisk, 2020; Heineke, Davin, & Dávila, 2019). As evidenced in this study using Honig's (2006) framework for policy implementation in practice, stakeholders appropriated the SoBL based on (a) policy goals and targets, such as Villa's focus on EBLs, (b) people involved in implementation, such as Walsh's work with community organizations, and (c) places where policy met practice, such as North's heritage and world‐language classrooms.…”
Section: Discussionmentioning
confidence: 92%
“…In this multiple case study of six districts spanning five states, we investigate how stakeholders implement the SoBL to promote biliteracy in their unique local contexts. Keenly aware of policy critiques and equity concerns for EBLs and speakers of less common languages, this study probes how districts work to equitably promote the award spanning bilingual, world language, and community language settings (Borowczyk, 2019; Colomer & Chang–Bacon, 2019; Heineke, Davin, & Bedford, 2018; Subtirelu, 2020; Valdés, 2020). We begin by describing our framework and methods to study SoBL implementation, followed by presentation and discussion of the resultant findings.…”
Section: Seal Of Biliteracy Policy Implementationmentioning
confidence: 99%
“…For another, because historically these communities have been bilingual, and many Latinx youth already navigate their lives bilingually, districts should not judge their bilingualism/biliteracy based on status-quo norms such as ''academic language'' (Flores & Rosa, 2015). Indeed, administrators and teachers need to question the acceptance of language assessments (Valde ´s, 2020), be critical of the Seal's codifying biliteracy (Colomer & Chang-Bacon, 2020) and vigilant about DL's logic of justice and its rewards. Spurning a compensatory-justice mentality that depicts the Seal as available to all to preempt concerns stemming from white entitlement, educators should create Seal policies that follow a distributive-justice logic which would have the Seal acknowledge Latinxs' biliterate repertoires and attend to the community's interests.…”
Section: Conclusion and Implications For Justicementioning
confidence: 99%